2011
DOI: 10.1039/c1cp20562e
|View full text |Cite
|
Sign up to set email alerts
|

The interface between Au(100) and 1-butyl-3-methyl-imidazolium-hexafluorophosphate

Abstract: The electrochemical interface of Au(100) and 1-butyl-3-methyl-imidazolium hexafluorophosphate has been characterized by cyclic voltammetry, electrochemical impedance spectroscopy and in situ STM, especially in two distinct potential ranges. In the vicinity of the potential of zero total charge--the value of which has been determined by immersion experiments--charging of the double layer is rather slow, it appears as if the ions comprising the ionic liquid would slowly exchange each other at the surface. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
109
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(123 citation statements)
references
References 35 publications
12
109
1
Order By: Relevance
“…The charging current measured on HOPG | BMIPF6 is lower by a factor of 3 to 5 compared to that measured on Au(100) | BMIPF6, 16 and the same applies for the dc capacitance -defined as the average charging current divided by the scan rate -, that has an approximate value of 7 μF/cm 2 .…”
Section: Cyclic Voltammetrymentioning
confidence: 79%
See 4 more Smart Citations
“…The charging current measured on HOPG | BMIPF6 is lower by a factor of 3 to 5 compared to that measured on Au(100) | BMIPF6, 16 and the same applies for the dc capacitance -defined as the average charging current divided by the scan rate -, that has an approximate value of 7 μF/cm 2 .…”
Section: Cyclic Voltammetrymentioning
confidence: 79%
“…11,12,13 From the fundamental research point of view, the key point of studying metal | IL interfaces is the use of electrodes with well-defined surface structures in combination with high-purity ILs. In accordance with this statement, the interface of gold single crystals with a well-defined surface orientation was recently studied in 1-butyl-3-methyl-imidazolium hexafluorophosphate (BMIPF6); 14,15,16 in a home-made guanidinium-based IL; 17 and in 1-butyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide (BMITf2N). 18 In these studies the Faradaic reaction-free potential regions of the metal | IL electrodes were identified and characterized by cyclic voltammetry (CV), while electrochemical impedance spectroscopy (EIS) was employed in order to determine the interfacial capacitance.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations